2006
DOI: 10.1002/bsl.689
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the association between apology and forgiveness amongst victims of human rights violations

Abstract: Forgiving may lead to an improvement of mental health, and from a therapeutic jurisprudence perspective it is important to establish what aspects of judicial procedures can be changed to promote forgiving. The literature suggests that receiving an apology may encourage forgiving. However, there is a dearth of empirical research regarding the association between forgiving and apology in judicial settings. This paper reports the findings of a study that examined the association between forgiving and four restora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 59 publications
4
71
0
1
Order By: Relevance
“…+P \ .10, *P \ .05, **P \ .01, ***P \ .001. 1 Model contains a statistically significant indirect effect amends, and assurances certainly facilitate the forgiveness process (Allan et al, 2006;Exline et al, 2003), but if these acts of contrition are viewed as necessary conditions or prerequisites required before forgiveness can be offered, then there will likely be fewer instances of forthcoming forgiveness for that individual. This is due simply to the fact that those who cause an offense will not always fulfill such conditions, regardless of their appropriateness, and the offended party does not have the power to make them occur.…”
Section: Conditional Forgiveness Of Others Predicts Mortalitymentioning
confidence: 98%
“…+P \ .10, *P \ .05, **P \ .01, ***P \ .001. 1 Model contains a statistically significant indirect effect amends, and assurances certainly facilitate the forgiveness process (Allan et al, 2006;Exline et al, 2003), but if these acts of contrition are viewed as necessary conditions or prerequisites required before forgiveness can be offered, then there will likely be fewer instances of forthcoming forgiveness for that individual. This is due simply to the fact that those who cause an offense will not always fulfill such conditions, regardless of their appropriateness, and the offended party does not have the power to make them occur.…”
Section: Conditional Forgiveness Of Others Predicts Mortalitymentioning
confidence: 98%
“…Except for Kanz's (2000) findings, the current study and previously reviewed research underlined the positive effects of an apology on forgiveness (Schmitt et al 2004;Gauche and Mullet 2005;McCullough et al 1997;Allan et al 2006). The expression of an apology indicates that the offender acknowledges the wrong done, and regrets having caused harm.…”
Section: Discussionmentioning
confidence: 48%
“…Reviewed research indicated that many people were dissatisfied with the way the church had handled the situation (Hoffman 2005;Morin and Cooperman 2002). Previous research on forgiveness showed that factors such as apology, reconciliation, frequency of the offensive act, and abuser's change of life, could influence the likelihood to forgive (Allan et al 2006;Kanz 2000;Schmitt et al 2004). The current study explores people's response to child sexual abuse by priests.…”
Section: The Current Studymentioning
confidence: 97%
“…As a consequence (and because reconciliation casts trauma not just as a symptom of past violence but as a potential cause of future violence) "curing" war trauma has become key to preventing its resurgence. In these contexts mental health practitioners have lent scientific credence to the idea that (1) forgiveness can improve mental health amongst victims (thus providing such a panacea) (Kaminer et al 2001), and as a result have (2) promoted the idea that judicial procedures should be changed in order to promote forgiveness amongst victims (Allan et al 2006). 15 Taken together, these studies help to advance a fascinating theory about the work of the TRC and other reconciliation processes where amnesty is a feature.…”
Section: The Therapeutic Ethos Pathologizes Human Behaviormentioning
confidence: 99%